Pengaruh Fear of Missing Out (FOMO) dan Sales Promotion terhadap Impulsive Buying Robux dengan Emosi Positif sebagai Mediator Parsial - Muhammad Syaroni; Aryanti Muhtar Kusuma (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to examine the role of positive emotions in mediating the effects of Fear of Missing Out (FOMO) and sales promotion on impulsive Robux purchasing in the Roblox application. This research employed a quantitative approach using path analysis. Data were collected from 251 Roblox users. The t-test results indicate that FOMO, sales promotion, and positive emotions each have a positive and significant partial effect on impulsive buying. Simultaneously, these three variables explain 75.8% of the variance in impulsive buying. The path analysis findings reveal that the direct effects of FOMO and sales promotion are stronger than their indirect effects through positive emotions. Thus, while positive emotions significantly mediate the relationship between the independent variables and impulsive buying, their role is not dominant. Impulsive purchasing among Roblox users is primarily driven by direct impulses stemming from the fear of missing out on trends and the attractiveness of sales promotions.